La teoria del sublime di Johann Jacob Bodmer e l’arte di Johann Heinrich Füssli (Materiali di Estetica. Terza serie, 2024)
Fuseli's education took place under the guidance of Bodmer, who introduced him to the reading of Pseudo-Longinus and the great works of world literature. From Bodmer he derived the idea that the artistic transposition of the so-called “violent” or “tumultuous” sublime produces pleasure mixed with displeasure. His painting was strongly influenced not only by ancient, Renaissance and Mannerist art, but also by physiognomy. After moving to London, he applied what he had learned in illustrating Shakespeare and Milton.
Keywords: Füssli; Bodmer; sublime